2012
DOI: 10.1007/s00432-012-1202-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of cytokeratin 17 expression with differentiation in oral squamous cell carcinoma

Abstract: PurposeThe aim of this study was to confirm the expression profile of cytokeratin (CK)17 in comparison with that of CK13 in oral squamous cell carcinoma (OSCC) and leukoplakia and to clarify an association of CK17 with the OSCC differentiation.MaterialsThe expression of CK17 and CK13 was immunohistochemically examined in 105 patients with OSCC and 108 patients with leukoplakia. A correlation of CK expression with clinicopathological variables was carried out. The over-expression levels of CK17 mRNA were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
85
2
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(132 citation statements)
references
References 30 publications
24
85
2
9
Order By: Relevance
“…Although many studies have claimed that CK13 (-)/CK17 (+) is the unique profile pattern of oral SCC (Mikami, Cheng et al 2011 ;Kitamura, Toyoshima et al 2012 ), we showed that CKs pattern for GCT-PCH is CK13 (-) /CK17 (+). CK is just a one example of the possible IHC similarity between PCH and oral SCC.…”
Section: Discussioncontrasting
confidence: 61%
“…Although many studies have claimed that CK13 (-)/CK17 (+) is the unique profile pattern of oral SCC (Mikami, Cheng et al 2011 ;Kitamura, Toyoshima et al 2012 ), we showed that CKs pattern for GCT-PCH is CK13 (-) /CK17 (+). CK is just a one example of the possible IHC similarity between PCH and oral SCC.…”
Section: Discussioncontrasting
confidence: 61%
“…Confirmation of these results was obtained by reverse transcription-quantitative polymerase chain reaction (RT-qPCR) (Toyoshima et al, 2009). Higher expression of K17 has also been reported in patients with stage I and II OSCC and in well-differentiated oral cavity carcinoma (Toyoshima et al, 2009;Kitamura et al, 2012).…”
Section: Discussionmentioning
confidence: 75%
“…Our results show that these keratins are highly expressed in tumoral tissue compared to non-tumoral surgical margins. Other studies have shown the presence of K17 in gastric adenocarcinoma, Ewing sarcoma, OSCC, and ovary, breast, and cervical cancers (Maddox et al, 1999;Ide et al, 2012;Kitamura et al, 2012;Alshareeda et al, 2013;Sankar et al, 2013;Wang et al, 2013). K19 expression was shown in liver, breast, lung, ovary, thyroid and oral cancers (Safadi et al, 2010;Isic Dencic et al, 2013;Kong et al, 2013;Liu et al, 2013;Park et al, 2013).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…TCO-1 JCRB0239 cells were established from a human nondifferentiated thyroid cancer 17 , the SAS JCRB0260 cell line was established from poorly differentiated OSCC of the tongue 18 , and the HO-1-u-1 cell line JCRB0828 was established from a poorly differentiated OSCC of the oor of the mouth 19 . EGCG MW458.37 was purchased from Wako Pure Chemical Industries Osaka, Japan .…”
Section: Cell Lines and Reagentsmentioning
confidence: 99%